Simulation with Visual SLAM and AweSim - Pritsker, A. Alan B. (Wiley,Systems Pub. Corp., 1999)
This book presents a process for problem resolution, policy crafting, and decision making based on the use of modeling and simulation. Detailed descriptions of the methods by which Visual SLAM and AweSim, version 3, support this process are presented. The text is organized into four parts: Introduction to Simulation, Visual SLAM Network Modeling and AweSim, Simulation Analysis, and Visual SLAM Discrete, Continuous and Combined Modeling.